2007
DOI: 10.1097/01.ccm.0000295593.25106.c4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of human peripheral blood mononuclear cells in severe human sepsis*

Abstract: Energetic failure of PBMCs in sepsis may be a factor associated with the modulation of immune response and human leukocyte antigen-DR phenotype, partially driven by plasma factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 34 publications
3
96
2
1
Order By: Relevance
“…In a recent study, we have also observed that mitochondrial function is altered in PBMCs following hemorrhagic shock and resuscitation in a rodent model (13). Similar to a report by Belikova et al (12), we found that PBMCs recovered mitochondrial function when incubated in serum from control animals with control PBMCs developed depressed function when incubated with serum collected following severe shock; suggesting a systemic factor may be responsible for mitochondrial dysfunction in PBMCs. However, the extent to which mitochondrial dysfunction in PBMCs parallels similar changes in other organ systems is not clear.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…In a recent study, we have also observed that mitochondrial function is altered in PBMCs following hemorrhagic shock and resuscitation in a rodent model (13). Similar to a report by Belikova et al (12), we found that PBMCs recovered mitochondrial function when incubated in serum from control animals with control PBMCs developed depressed function when incubated with serum collected following severe shock; suggesting a systemic factor may be responsible for mitochondrial dysfunction in PBMCs. However, the extent to which mitochondrial dysfunction in PBMCs parallels similar changes in other organ systems is not clear.…”
Section: Introductionsupporting
confidence: 91%
“…In particular, PBMC respiratory function may reflect disease severity in sepsis (12) and we have noted that PBMC mitochondrial function is dramatically altered during hemorrhagic shock and resuscitation (13). As such, monitoring PBMC respiratory capacity may provide a minimally invasive surrogate for end-organ mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigations have demonstrated reduced function of different aspects of mitochondrial respiratory activity of peripheral blood immune cells (PBICs) in the early disease stages of sepsis patients admitted to the ICU [9-11]. The results are, however, somewhat divergent, probably reflecting differences in study population, experimental setup, and what mitochondria-specific markers have been chosen for normalization of respiration to cellular content of mitochondria.…”
Section: Introductionmentioning
confidence: 99%